Association Between the 7‐Day Moving Average for Nutrition and Growth in Very Low Birth Weight Infants. Issue 4 (22nd December 2017) - Falciglia, Gustave H.; Murthy, Karna; Holl, Jane; Palac, Hannah L.; Oumarbaeva, Yuliya; Yadavalli, Pratyusha; Woods, Donna; Robinson, Daniel T.
Abstract: Background : Very low birth weight (VLBW) infants remain at risk for postnatal growth restriction. Clinicians may have difficulty identifying growth patterns resulting from nutrition interventions, impeding prompt management changes intended to increase growth velocity. This study aimed to quantify the association between growth and nutrition intake through 7‐day moving averages (SDMAs). Methods : The first 6 weeks of daily nutrition intake and growth measurements were collected from VLBW infants admitted to a level 4 neonatal intensive care unit (2011–2014). The association between SDMA for energy and macronutrients and subsequent 7‐day growth velocities for weight, length, and head circumference were determined using mixed effects linear regression. Analyses were adjusted for fluid intake, infant characteristics, and comorbid conditions. Results : Detailed enteral and parenteral caloric provisions were ascertained for 115 infants (n = 4643 patient‐days). Each 10‐kcal/kg/d increase over 7 days was independently associated with increased weight (1.7 g/kg/d), length (0.4 mm/wk), and head circumference (0.9 mm/wk; P < .001, for weight and head circumference; P = .041 for length). Each 1 g/kg/d macronutrient increase was also associated with increased weight (protein, P = .027; fat and carbohydrates, P < .001), increased length (fat, P = .032), and increased head circumference (fat and carbohydrates, P < .001). Conclusions : The SDMA identifies clinically meaningful associations among total energy, macronutrient dosing, and growth in VLBW infants. Whether SDMA is a clinically useful tool for providing clinicians with prompt feedback to improve growth warrants further attention.